As categorias do trabalho e da reprodução como constituintes do ser social a partir do pensamento de György Lukács - Lemos, Jessica Holanda (2023)
Lukács, like Marx, attributes to work a conditio sine qua non for analyzing the genesis and development of human sociability. In this way, work corresponds to the foundation of the social being, since it enables a double transformation: that of nature into something new and of man into a social being. By giving a particular focus to work in his work Ontologia do Ser Social, Lukács, analyzing the ontological leap from the organic being that is found at its merely biological level to the social being, as well as the various forms of sociability, draws attention to the fact that the complex of work is not isolated in relation to other spheres of society and that the interrelationship with the category of reproduction must be taken into account, since it is through it that the work process takes place, given that everything that has been acquired based on the relationship between man and nature, knowledge, skills and experiences must be passed on to other men, to future generations. Based on these considerations, the objective of this research is to demonstrate the intrinsic relationship between the work complex and the reproduction complex, since both are directly related to the formation of the social being. Taking mainly Lukács' thought, we can say that such categories compose the fundamental structures for the genesis of the social being and, consequently, for the development of the human race. Thus, we raise the hypothesis that although work is a central category in Lukács' Ontology, we also consider that the category of reproduction deserves its prominent place, since the constitution of men's social life is only effective through the intrinsic relationship between work and reproduction as essential categories that are responsible for the genesis and development of the social being. We can conclude that it is in this sense that Lukács attributes to reproduction a role as relevant as work, since it is through reproduction that work takes effect and enables the constitution of the social being and, consequently, of humankind by allowing both the continuity of the social being as of society itself.